Human airway organoids as 3D in vitro models for a toxicity assessment of emerging inhaled pollutants: Tire wear particles - Jiang, Yingying; Lu, Lin; Du, Chao; Li, Yanting; Cheng, Wenting; Bi, Huanhuan; Li, Guo; Zhuang, Min; Ren, Dunqiang; Wang, Hongmei; Ji, Xiaoya (Frontiers in Bioengineering and Biotechnology, 2023)
Three-dimensional (3D) structured organoids have become increasingly promising and effective in vitro models, and there is an urgent need for reliable models to assess health effects of inhaled pollutants on the human airway. In our study, we conducted a toxicity assessment of human airway organoids (hAOs) for tire wear particles (TWPs) as an emerging inhaled pollutant. We induced primary human bronchial epithelial cells (HBECs) to generated human airway organoids, which recapitulated the key features of human airway epithelial cells including basal cells, ciliated cells, goblet cells, and club cells. TWPs generated from the wearing of tire treads were considered a major source of emerging inhaled road traffic-derived non-exhaust particles, but their health effect on the lungs is poorly understood. We used human airway organoids to assess the toxicology of tire wear particles on the human airway. In an exposure study, the inhibitory effect of TWPs on the growth of human airway organoids was observed. TWPs induced significant cell apoptosis and oxidative stress in a dose-dependent manner. From the qPCR analysis, TWPs significantly up-regulated the expression pf genes involved in the inflammation response. Additionally, the exposure of TWPs reduced SCGB1A1 gene expression associated with the function of the club cell and KRT5 gene expression related to the function of basal cells. In conclusion, this was first study using human airway organoids for a toxicological assessment of TWPs, and our findings revealed that human airway organoids provide an evaluation model of inhaled pollutants potentially affecting the lungs.